2020
DOI: 10.1038/s41598-020-69033-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the pathogenic SNPs in BLM helicase and their biological consequences by computational approach

Abstract: The BLM helicase protein plays a vital role in DNA replication and the maintenance of genomic integrity. Variation in the BLM helicase gene resulted in defects in the DNA repair mechanism and was reported to be associated with Bloom syndrome (BS) and cancer. Despite extensive investigation of helicase proteins in humans, no attempt has previously been made to comprehensively analyse the single nucleotide polymorphism (SNPs) of the BLM gene. In this study, a comprehensive analysis of SNPs on the BLM gene was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 112 publications
1
20
0
Order By: Relevance
“…With the advancement of high-throughput "omics" technology and computational methods, the gene expression and protein interaction data could be integrated at the systems biology level to identify the altered gene regulatory network, activated pathways, and the molecular mechanism underlying complex genetic and infectious diseases (18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of high-throughput "omics" technology and computational methods, the gene expression and protein interaction data could be integrated at the systems biology level to identify the altered gene regulatory network, activated pathways, and the molecular mechanism underlying complex genetic and infectious diseases (18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…Both high and low levels or loss of BLM may lead to genomic instability and may eventually promote tumorigenesis. [15,6]Although recent evidence shows BLM mRNA to be over expressed in various cancers including colon, breast and prostate when compared with the normal samples. [16,18,13] However, the roles of BLM in human pan-cancer are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…[13,14] Otherwise, Alzahrani et al found that BLM overexpression was also related to poor survival in lung and gastric cancer patients. [15]Moreover, BLM mRNA and protein levels are found to be overexpressed in patients with colorectal cancer. [16,17] Furthermore, accumulative evidences suggest that a significant BLM mRNA over-expression along with high BLM cytoplasmic localization has been associated with poor breast cancer-specific survival.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported several SNPs that associated with cancer (Alzahrani et al, 2020 ; Hawsawi et al, 2019 ; Semlali, Almutairi, et al, 2018 ; Semlali, Parine, et al, 2018 ). This in silico study aimed to predict the interaction of TEX19 with LIRE1 and the role of TEX19 gene polymorphisms in the stability of produced protein and the interaction with LIRE1.…”
Section: Introductionmentioning
confidence: 97%